Energy potentials of military buildings - Živković, Miladin Z.; Banjac, Goran M. (Vojnotehnički glasnik / Military Technical Courier, 2015)
The economic crisis, extremely large budgets for providing necessary energy and the adopted legislation in the field of energy impose the necessity of finding and implementing positive solutions in order to achieve a proper and desirable degree of energy efficiency. This paper presents a preliminary analysis of the prescribed legislation in the field of energy - energy efficiency as well as the analysis of the reports on problems in construction engineering and projects used to solve energy problems in buildings. To obtain preliminary data of the financial effects of the implementation of positive solutions for improving the energy efficiency of buildings, a non-professional software package was used and the results obtained were within the framework of the national average for buildings of the same age. The structural characteristics of a building in question and its geographical location point to its specific potential for using renewable energy sources. The paper has shown that there is a legal obligation for the energy retrofit of a building used by the Army of Serbia as well as preliminary economic effects of the energy retrofit project realization and utilization of renewable energy sources. Introduction Economic crises create a number of problems which impose a need for identifying internal potentials of all types of organizations in order to overcome them. This paper deals with the energy problems of buildings in use in the Army of Serbia and with possibilities for overcoming them while achieving long-term economic benefits. Theoretical determination of the paper subject Building categorization In order to precisely define construction types to which this paper refers to, buildings taken into consideration are categorized and classified relating to their purpose, energy efficiency and life time. Energy efficiency Energy efficiency represents the thermal characteristics of a building through the energy required to provide prescribed conditions of comfort. The evidence of specific energy performances of buildings is verified by an energy passport. Legal aspects of energy efficiency By signing the Treaty of Establishing the Energy Community of South East Europe, the Republic of Serbia has accepted the obligations of the contract and started the harmonization of its legal framework through providing support for the implementation of regulations on energy, environmental protection, competition and strengthening of the electricity market. Thermal insulation Thermal insulation usually refers to various kinds of insulating products of thermal insulation materials as well as to the process of thermal insulation of buildings. Materials for thermal insulation All insulation materials are classified according to: the origin of raw materials for production, the value of the coefficient of thermal conductivity, the density value and the places and methods of their application. Thermal insulation of buildings Thermal insulation of buildings includes a series of measures and activities from the design phase to facade finishing with a view to reducing heat losses. On existing buildings, typical heat losses are in the range from 10 to 40%, depending on structural elements. Thermal insulation is realized through the project of energetic rehabilitation of buildings. Renewable energy sources Renewable energy sources are all non-fossil energy sources, and the estimated total available technical potential of renewable energy sources in the Republic of Serbia is 5.56 million tons of oil equivalent. The obligation of each subject in the chain of production - energy consumption is to find and implement technical solutions for the utilization of locally available renewable energy sources. The current state of energy efficiency in buildings The average age of buildings in Serbia is approximately 41 years, with more than 62% of them made before 1980s under practically nonexistent energy regulations. Existing experience and analyses of the effects of increasing thermal insulation have shown that energy activities should be focused primarily on the rehabilitation of buildings built before 1987 where it is possible to achieve savings in energy consumption of about 70%. A preliminary assessment of the effects of energy rehabilitation According to the preliminary evaluation of the building in question and the average age of buildings in use in the Army of Serbia, it was determined that the building belongs to the category of objects for which: there is legal obligation to issue the energy passport; it is recommended to undertake energetic rehabilitation with the best outcome, and it is possible to implement not only energy rehabilitation but also capacities for renewable energy sources in order to achieve additional economic gain. Conclusion This paper presents a preliminary analysis of a concrete building through the prism of current legislation in force. A simplified comparative analysis with similar objects and the usage of simple software packages very easily showed that the energy potential of the observed building is not that small. However, the result of this work has only tackled the problem of energy inefficiency in buildings in the use in the Serbian Army and opened a number of new issues in this area.